Improvements in investment attractiveness of Ukraine - Paimanova, V. A. (ХНУ ім. В. Н. Каразіна, 2012)
The paper analyses the situation on Ukrainian stock market in the context of economic crisis. The work provides research on possible ways of investment in Ukrainian economy, particularly in such fields as building and agriculture; analysis of possible involvement of new potential investors (in case of China and Arab countries); description of activities taken by the State concerning improvement of investment attractiveness of Ukraine.
Данная статья посвящена рассмотрению сложившегося вследствие экономического кризиса положения на фондовом рынке Украины. Структура работы предусматривает рассмотрение возможных направлений инвестирования в украинскую экономику, в частности в такие области, как строительство и сельское хозяйство, анализ возможности привлечения новых потенциальных инвесторов (на примере Китая и арабских стран). Также проанализированы мероприятия, осуществляемые государством по повышению инвестиционной привлекательности Украины.
Keywords: investment attractiveness; investors; stock market; ways of investment